METASTATIC PULMONARY NEUROENDOCRINE NEOPLASM WITH CARCINOID SYNDROME COMPLICATED BY BOWEL PERFORATION - Khoo, Yong Ming; Teo, Wee Jing; Lian, Zi Yang; Hussein, Zanariah Binti (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Carcinoid syndrome (CS) results from hormone-secreting neuroendocrine neoplasms (NENs) releasing bioactive sub- stances into systemic circulation. NENs are most commonly found in the gastrointestinal tract and less frequently in the lungs. CS develops in about 19% of patients with NENs, with 20% presenting with distant metastases. Rarely, mesen- teric fibrosis in CS can lead to ischemia and perforation. We present a case of metastatic bronchial NEN with CS, complicated with bowel perforation and subsequent death. CASE A 46-year-old male with previous history of spinal surgery for a post-traumatic compression fracture presented with gradual bilateral lower limb weakness and back pain, followed by chronic diarrhea and significant weight loss. Spinal MRI revealed extensive metastatic bone disease. Oesophagogastroduodenoscopy (OGDS) and colonoscopy were unremarkable; however, CT imaging identified a solitary endobronchial mass in the left lower lobe (3.1 x 2.6 x 2.8 cm), associated with left hilar lymphadenopathy and liver metastases. Biopsy of the lung mass revealed a grade 1 neuroendocrine tumor (Ki67 1%). Urinary 5-hydroxyindolacetic acid (5- HIAA) levels were markedly elevated at 854.6 µmol/day. Gallium-68 DOTATATE PET-CT demonstrated somatostatin receptor-avid disease involving the left lung, with media- stinal nodes, liver and extensive skeletal metastasis. A diagnosis of CS was established based on clinical presen- tation, elevated 5-HIAA, imaging, and histopathology. The patient was initiated on octreotide, a somatostatin analogue. However, he struggled to come to terms with the diagnosis and self-discharged against medical advice. He was later readmitted with severe hypokalemia, acute kidney injury, metabolic acidosis and acute abdomen. CT imaging revealed pneumoperitoneum consistent with a perforated duodenum. Due to hemodynamic instability, surgical intervention was not feasible, and palliative care was given. CONCLUSION This case illustrates a rare and potentially fatal complication of CS, underscoring the importance of early diagnosis and prompt treatment. Maintaining a high index of suspicion is crucial for timely identification of CS.